Carotid body tumors: what have we learned in 5 years? - Cobanoglu, Bengu; Arslan, Selcuk; Bahadır, Osman; Umit Isık, Abdulcemal; Imamoglu, Mehmet (ENT Updates, 2020)
Objective: Objectives: The present study aimed to retrospectively evaluate patients who were operated for carotid body tumors (CBT) in our clinic. Methods: The present study involved 19 patients who underwent surgical CBT removal in the Otorhinolaryngology- Head and Neck Surgery Department of Karadeniz Technical University Medical Faculty between 2013 and 2018. Sociodemographic characteristics, clinical presentation and findings of physical examination, Shamblin classifications based on preoperative radiological images, surgical procedure, histopathological diagnosis and complications were recorded from hospital records. Results: Seven of the patients were male and 12 were female. The mean age of the patients was 48.8 years and the most frequent symptom was a painless mass in the neck. According to the Shamblin classification, seven of our patients had Shamblin type I, nine patients had Shamblin type II and three patients had Shamblin type III tumors. Twelve patients had preoperative embolization of the tumor and seven patients were operated without embolization. Three patients had intraoperative carotid artery injury-related complications, whereas one patient had weakness in tongue movements due to hypoglossal nerve paresis. Conclusion: The main treatment for CBT is surgery, however, preoperative embolization is still controversial. Successful management of patients with CBT can be achieved via a multidisciplinary approach with the participation of head and neck surgery, cardiovascular surgery and radiology departments.